Existence of solution sets for Φ-Laplacian for random impulsive differential equations - Mohamed Ferhat; Fatima Zohra Ladrani; Mohamad Biomy; Abdelkader Moumen; Hicham Saber; Tariq Alraqad (Alexandria Engineering Journal, 2024)
In this article, we provide results on the existence and compactness of the set of solutions for a class of initial-value problem representing a first-order random impulsive differential equation. The key tool to achieve our goal is based on an alternative nonlinear Leary-Schauder type theorem in the settings of generalized Banach spaces.